Analisis Pseudo-Thinking dalam Pemecahan Masalah Matematis Berbasis Etnomatematika Pada Siswa Ditinjau dari Gaya Kognitif - Devia Meisya Badar; Kamid; Khairul Anwar (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
The research to find out and describe the results of the pseudo-thinking process in solving ethnomathematics-based mathematical problems in students in terms of cognitive style. The methods used in this study are qualitative descriptive. The subjects of this research were junior high school students from each field independent and field dependent cognitive style. The total number of respondents was 4 students. Data collection techniques using test mathematics problem solving based on ethnomathematics, interviews, and documentations. Based on the research result, it was found that 1) two students who classified field independent cognitive style are experiencing pseudo right or pseudo false and 2) two students who classified field dependent cognitive style are experiencing pseudo right or pseudo false.